New Directions in Nutrition. - Ghosh, Shibani; Webb, Patrick. (Tufts University. Tisch Library., 2018)
This presentation was given in Washington DC at a USAID tri-Innovation lab event: Advancing the Global Food Security Strategy: Insights from three Innovation Labs on food security, gender and nutrition. It centers possibilities emerging from new data, but stresses the need for further research so outcomes are more conclusive.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy